Oil palm cultivation and social indicators of independent smallholders in pompa air: A review - Ernawati Hamid; Mirawati Yanita; Zulkifli Alamsyah (Agriekonomika, 2022)
This study aims to describe the independent smallholders' oil palm farming and the social conditions of the ISPO-certified farmers. who are members of KUD Mutiara Bumi. Descriptive and quantitative data were used to describe oil palm farming and the social needs of independent smallholders who received ISPO certificates. The results showed that the average oil palm production was 23,788 Kg/Ha/Year with an average selling price of IDR. 1,578/Kg. The land use is 3.12 Ha/Farmer, the number of trees is 132/Ha, fertilizer 920 Kg/Ha/Year, pesticides 8.02 litre/Ha/Year, and labour is 64.46 working days/Ha. For comparison, the measurement of farmer social studies consists of livelihood, education level, housing, and consumption patterns. Therefore, each hand was classified with the appropriate category, except for livelihood and education indicators. Ownership of an ISPO Certificate requires a commitment to maintaining compliance with standards and improving social indicators.